PEMBELAJARAN BERBASIS SENTRA IMTAQ DALAM PENGENALAN NILAI AGAMA DAN MORAL ANAK USIA DINI DI TAMAN KANAK-KANAK ISLAM TERPADU AL AZKA KOTA JAMBI - Ernawati (Pt. Anagata Sembagi Education, 2024)
The purpose of this study aims to find out how the teacher's efforts in the application of Imtaq center-based learning, how the teacher's efforts in introducing religious and moral values of children as well as supporting and inhibiting factors in learning and religious values in Al Azka Integrated Islamic Kindergarten, Jambi City. Research methods use a qualitative approach. Data collection is carried out by observation, interviews and documentation. Data analysis using Miles and Huberman's model is data reduction, data presentation, data verification and conclusion drawing. The location of the study was conducted at Al Azka Integrated Islamic Kindergarten, Jambi City. The results of this study that Al Azka Kindergarten in Jambi city in the use of their Imtaq center is very good in increasing the recognition of religious and moral values of students, especially in memorizing prayers in daily life and also memorizing hadith. This can also be seen from the enthusiasm of the students in participating in learning. The conclusion of the findings of this study is that this research can be used as input in increasing the faith and piety of students through the use of the Imtaq center. In addition, the findings in this study are also expected to increase the knowledge and skills of teachers in applying a learning process that is much more effective, creative and more enjoyable for students in an effort to improve learning in early childhood education.